2015
DOI: 10.1086/679595
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic and biogeochemical influences on carbon processing in the riparian zone of a subarctic stream

Abstract: Small streams and their adjacent riparian zones contribute disproportionately to the processing and transport of C compared to the catchment area and, thereby, may alter the flux of dissolved organic C (DOC) from aquatic ecosystems. We examined the factors influencing C uptake and CO 2 production in the riparian zone of a boreal stream. We tested the hypothesis that enhanced water velocity increases the supply of DOC and nutrients to microorganisms and, therefore, enhances DOC mineralization in the riparian zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In addition, previous studies in similar rivers have shown that the combined biological and photochemical degradation of DOC within the stream channel is insufficient to account for the observed CO 2 fluxes (Lapierre and del Giorgio, 2014). It is thus clear that most of the degradation of terrestrial DOC must occur before it reaches the river channel, likely in the hyporheic zone, which is known to be a hotspot of biogeochemical activity (Fiebig et al, 1990;Krause et al, 2011;Rinehart et al, 2015;Schindler and Krabbenhoft, 1998;Stegen et al, 2016). In this regard, the DOC removal that we observe here is commensurate with what has been reported for artificial stream bed reactors (Sleighter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies in similar rivers have shown that the combined biological and photochemical degradation of DOC within the stream channel is insufficient to account for the observed CO 2 fluxes (Lapierre and del Giorgio, 2014). It is thus clear that most of the degradation of terrestrial DOC must occur before it reaches the river channel, likely in the hyporheic zone, which is known to be a hotspot of biogeochemical activity (Fiebig et al, 1990;Krause et al, 2011;Rinehart et al, 2015;Schindler and Krabbenhoft, 1998;Stegen et al, 2016). In this regard, the DOC removal that we observe here is commensurate with what has been reported for artificial stream bed reactors (Sleighter et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…CPCRW is approximately 10 600 ha in size and divided into 11 watershed units. Many research initiatives at CPCRW involve vegetation and hydrology comparisons among watershed units (Amatya et al, 2016;Rinehart et al, 2015;Tanaka-Oda et al, 2016). Upland areas are dominated by paper birch and aspen on south-facing slopes.…”
Section: Study Sitesmentioning
confidence: 99%
“…DOC processing in these zones must be better understood to predict effects of permafrost thawing associated with climatic warming on DOC fluxes. Rinehart et al (2015) used push-pull slug tests with acetate to investigate the effects of GW-SW interactions on DOC processing in the riparian zone of a boreal catchment. The rate constants for DOC processing did not appear to be related to preinjection water chemistry.…”
Section: Geochemistry and Biogeochemistrymentioning
confidence: 99%